Investor protection, prospect theory, and earnings management: An international comparison of the banking industry - Shen, Chung-Hua; Chih, Hsiang-Lin (Journal of Banking & Finance, 2005)
This paper raises three issues related to the earnings management (EM) of banks across 48 countries. First, does earnings management of banks exist in all 48 countries? Second, what is the incentive of banks to manage earnings? Third, why does EM vary across countries? To answer these three questions, two thresholds (viz., a threshold of zero earnings and a threshold of zero earnings change) are employed. The answer to the first question above is that banks in more than two-thirds of the 48 countries sampled are found to have managed their earnings. With respect to the second question, prospect theory is used to provide an answer. The relationship between return and risk is positive for high earnings groups, but is negative for low earnings banks. Finally, as to the last question, stronger protection of investors and greater transparency in accounting disclosure can reduce banks’ incentives to manage earnings. Also, higher real GDP per capita decreases the degree of earnings management. It is seen that stronger enforcement of laws can counter intuitively result in stronger earnings management. However, this effect appears in low-income countries only, and not in high-income countries.